Monitoring overtourism : : Destination Management Systems as a way forward (Bangladesh Journal of Public Administration, 2021)
Destination Management Systems (DMS) come up with comprehensive and latest statistical data on a particular or numerous tourist destinations. DMS make a widespread set of tourism supervision, advancement and fulfillment tools obtainable with tourism products and services, and tourist databases as its basis. However, the core objective of this research is to put forward a common DMS together with sub-systems of DMS to the tourism destinations in Bangladesh to make sure proper tourism administration, particularly in the over-tourists places, by using this common podium. Therefore, the study has been conducted using qualitative case study approach. Focus Group Discussion has been conducted among the technology experts, tourism specialists, concerned government bodies, tourist police and other stakeholders. In addition, interviews among associated destination management organizations with structured questionnaire have been taken to embody the idea. DMS are of great use to manage the tourist flow and to have appropriate statistics. It helps to connect with national server to put a ceiling on number of visitations in an area. This platform can be used for both marketing and de-marketing of destinations according to individual situations. Categorizing tourists, their preferences, characteristics and most importantly to lessen the seasonality of tourism business this system is indispensable. Furthermore, this research can overlay the way onward to have suitable management over the tourism systems in Bangladesh by providing required guidelines to form and maintain DMS entirely.